REVEALED COMPARATIVE ADVANTAGE IN SOY EXPORTATION BETWEEN THE MAIN EXPORTERS IN BRAZIL/Vantagens comparativas reveladas da exportação de soja entre os principais exportadores do Brasil - Haliski, Daniele Sedorko; Oliveira, Renato Alves; Santos, Jeronimo Alves (Informe GEPEC, 2020)
The objective of this work was verify the existence of Revealed Comparative Advantages for the export of soy beans produced in the states of Mato Grosso, Paraná, Rio Grande do Sul, Goiás and Mato Grosso do Sul, in relation to Brazil, in the years 2006 to 2016. The Revealed Comparative Advantage Index (IVCR) was initially used, however, because the index was asymmetric for values greater than unity, the Symmetric Revealed Comparative Advantage Index (IVCRS) was used, since in this index values vary between -1 and 1. The results indicate that all the states studied had an advantage in exporting soy beans. However, it was observed that the southern states presented a period of increase and later reduction in the IVCR, and the states of the Midwest region suffered only a reduction in the IVCR, possibly because soy bean products were losing a little of the representation in total exported. Finally, it was concluded that even though there are government incentives to export products such as soy beans, Brazil still faces problems with the flow of agricultural production, low storage capacity and port in efficiencies.